101 Anti-EBNA1 molecular mimicry initiates cross-reacting autoantibodies in Systemic Lupus Erythematosus (SLE) & Multiple Sclerosis (MS). (14th December 2022) - Harley, John B; Clark, Dennis H; Chepelev, Iouri
Abstract : Recent results 1-3 support the hypothesis that SLE & MS autoantibodies arise from the anti- EBNA1 heteroimmune response. For example, SLE anti-SmB/B' autoantibodies appear to begin with a proline rich sequence from EBNA1 that differs from the SmB/B' sequence by one amino acid (figure 1). Other SLE & MS autoantibodies also cross-react with other EBNA1 structures. Some MS autoantibodies bind the surface protein, glialCAM, and destroy nerve cells. Autoanti- glialCAM also bind a neighboring proline-rich EBNA1 sequence (figure 1). The autoanti- glialCAM is a low Ig concentration MS response, while autoanti-SmB/B' is a high concentration Ig SLE response. EBNA1 has multiple molecular interaction strategies that result in virtually no EBNA1 peptides being presented on the surface of the EBV infected B cells. In the meantime, the 295 amino acid Glycine-Alanine repeat domain generates T cell independent antibody responses that epitope spread. In SLE four EBNA1 cross-reacting epitopes are known (SmB', SmD, C1q, and 60 kd Ro); four are also known for MS (GlialCAM, myelin basic protein, αB Crystallin, and Anoctamin 2). These observations suggest a general mechanism: That the anti-EBNA1 heteroimmune response is a REQUIRED step through which pathogenic autoimmunity is generated for most if not virtually all SLE & MS patients. If so, then the frequency of anti-EBNA1 antibody generation would be higher in SLE & MS patients than in controls. We show that this prediction is true for both SLE & MS, there by supporting the model (figure 2) and further suggesting that the anti- EBNA1 heteroimmune response may be a required step of a general mechanism for some patients to other idiopathic diseases, such as pre-eclampsia and rheumatoid arthritis. References: Laurynenka V, et al . Front Immunol 2022;13 :830993. McClain MT, et al. Arthritis Rheumatol 2006;54 :360. Lanz TV, et al. Nature 2022;603 :321.